Mikrozonasi di Daerah Plampang, Nusa Tenggara Barat - Iswanto, Eko Rudi; Riyanto, Theo Alvin; Suntoko, Hadi (EKSPLORIUM, 2021)
Nusa Tenggara Barat (NTB) Province is an area with intense seismic activity. This phenomenon is caused by tectonic activity as the result of the convergency of the Eurasia-Australia Plates (subduction zone) in the south and the Flores Fault in the north as well as the presence of local faults. Regarding the plan to develop the Samota area in Sumbawa Island, NTB, a study concerning earthquakes should be done. The purpose of this study is to map the seismic vulnerability index (Kg) through microtremor measurement by using the Horizontal to Vertical Spectral Ratio (HVSR) analysis method. The result of the study is a seismic vulnerability map of the Plampang area which its northern part has a low seismic vulnerability index indicated by the amplification factor value of less than three compared to other areas. The geology of the northern part of the Plampang area consists of volcanic rocks which has hard rock characteristic, very thin sediment thickness, and composed of Tertiary or older rocks. Seismic vulnerability maps can be useful as a reference for earthquake mitigation to reduce its risks.